The relationship between triglyceride, cholesterol and lipoprotein levels, and immune responses to hepatitis B vaccine - Guo, Dan; Dai, Jiazhen; Ju, Rong; Zhou, Qifan; Wang, Nenghuan; Wu, Chunhua; Tao, Hui; Jing, Hui; Zhu, Chen; Mao, Jinxian; Xu, Jiayan (Frontiers in Medicine, 2023)
Cholesterol homeostasis disorder and hypertriglyceridemia, as common metabolic 23 conditions, have rarely been reported to affect the immune responses to the hepatitis B vaccine. 24 Our study found that higher high-density lipoprotein (HDL)level showed a significant relationship 25 with positive anti-HBs results (cOR = 1.479, 95% CI: 1.150, 1.901, P= 0.002; aOR = 1.304, 95% CI: 26 1.006, 1.691, P = 0.045), especially in individuals aged 18- to 40-year-old, female, smoking more 27 than 100 cigarettes in life, and drinking more than 12 times every year. Lower low-density 28 lipoprotein (LDL) level was associated with a negative anti-HBs result among participants aged 29 18- to 40-year-old, and participants who were obese.Higher level of HDL and lower level of LDL 30 may be protective factors of better immune effect of hepatitis B vaccine. More research should 31 be conducted to investigate the influence of the cholesterol level on the immune responses to 32 the hepatitis B vaccine, and more in-depth research should be performed to uncover the 33 mechanism.